Financial sustainability of SMEs through Islamic crowdfunding - Haron, Razali; Md Husin, Maizaitulaidawati (IGI Global, 2019)
Recent years have witnessed the growth of Islamic crowdfunding from its mere existence to successfully distinguishing itself from conventional crowdfunding. The concept of crowdfunding is known as a practice of funding a project or venture by raising small amounts of money from many people, typically via the Internet. The concept of crowdfunding has gained popularity worldwide as an alternative source of financing, especially among small businesses which include small and medium enterprises (SMEs). As SMEs continuously face lack of financing which may hinder their business growth, it is projected that the emerging crowdfunding model may help solve this problem while at the same time sustain SMEs’ financial suitability. In this chapter, the concept of Islamic crowdfunding, crowdfunding models, the benefits and weaknesses of crowdfunding for SMEs, the applicability of crowdfunding towards driving financial sustainability initiatives for SMEs and issues for future research are discussed.